The Development Backwardness of Makassarese Coastal Community in South Sulawesi, Indonesia: A Study of Historical Sociology - Wahab, Abdul (TAWARIKH, 2013)
ABSTRACT: Indonesia as one of the countries in the world which has a vast sea or territorial waters wider than the mainland. Therefore, the marine potentials should be resources that contribute to national development. In fact, the national development carried out more oriented to the creation of economic growth centers in the major cities and ignores to develop the coastal communities. This is the starting point of problem in the history of Indonesia development, so that coastal communities, including the coastal communities of Makassar city, experiencing lag. Beside unfavorable orientation in national development, the socio-cultural factors of coastal communities also creates stagnant from generation to generation. Since the New Order regime (1966-1998), through the development program of coastal community has been implemented, the overall performance of the development of coastal and marine community has not shown any innovation or completion of deficiencies for coastal communities. Orientation of development from central to regional area (top down) shows that how development the coastal communities is not seen as a sector that could increase foreign exchange. Therefore, the data on potential sources of marine coastal communities, in the economic perspective, can be a mainstay for a large source of revenue. Finally, backwardness of Makassar coastal communities need reorientation and integrated development policies from the government and non-governmental organizations so that the history of development coastal communities are not repeated and it will consequently fail.KEY WORDS: Economic development, backwardness, coastal communities, Makassar city, attitude and mentality, community empowerment, and welfare and social justice.About the Author: Abdul Wahab, M.Si. is a Senior Lecturer at the Faculty of Education and Teacher Training UVRI (Veteran University of the Republic of Indonesia), Campus II UVRI Makassar, Jalan Baruga Raya, Antang, Makassar, South Sulawesi, Indonesia; and Doctoral Student at the Postgraduate Program UNM (State University of Makassar). For academic interest, he can be reached at: andy.wahab@gmail.comHow to cite this article? Wahab, Abdul. (2013). âThe Development Backwardness of Makassarese Coastal Community in South Sulawesi, Indonesia: A Study of Historical Sociologyâ in TAWARIKH: International Journal for Historical Studies, Vol.5(1) October, pp.117-126. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980.Chronicle of the article: Accepted (August 27, 2013); Revised (September 29, 2013); and Published (October 28, 2013).